ENDOCRINE ASPECTS OF AMIODARONE THERAPY IN CLINICAL PRACTICE (FOLLOW-UP AND TREATMENT ALGORITHM FOR PATIENTS WITH THYROID DYSFUNCTION) - N. Yu. Sviridenko; N. M. Platonova; N. V. Molashenko; S. P. Golitsyn; S. A. Bakalov; S. E. Serdyuk (Российский кардиологический журнал)
This review discusses the effects of amiodarone on thyroid function and summarises the results of international studies and the evidence obtained by the researchers from the A.L. Myasnikov Research Institute of Clinical Cardiology and Endocrinology Research Centre. The guidelines on thyroid dysfunction diagnostics and therapy, as well as the follow-up of amiodarone-treated patients, are presented.